Characterization and growth optimization of marine fungi, and antibacterial and biofilm removal activities of its extracts - Mat Daud, Noor Ifatul Hanim (2016)
Marine derived fungi known as source of bioactive compounds and many were found to produce compounds with antibacterial and biofilm removal activities. The objectives of this study are; 1) to characterize fungal isolates, 2) to study the effect of media, temperature and salinity on fungal growth, 3) to determine antibacterial activity of marine fungal extracts against food-borne bacteria; Staphylococcus aureus, Listeria monocytogenes, Escherichia coli and Salmonella typhimurium and 4) to examine biofilm removal activity of marine fungal extracts. Four fungal isolates; PR1T4, PP2L4, PR3T13 and PR5T4 isolated from Pulau Redang and Pulau Payar Marine Parks, Malaysia, were characterized using morphological and molecular identification. All isolates were subjected to study of the effect of media (PYGA, MEA and PDA), temperatures (25°C and 37°C) and salinities (0% and 15% of NaCl) on their growth. Antibacterial activity of all fungal extracts was tested against the selected bacteria using agar well diffusion assay. Test surface was done on stainless steel disc (SSD); adhesion, detachment and biofilm formation of tested bacteria. Screening of fungal extracts potential as biofilm removal agents was done against tested bacteria. The isolates were identified as Penicillium citrinum (PR1T4), Sarocladium strictum (PP2L4), Aspergillus sydowii (PR3T13) and Aspergillus species (PR5T4). All isolates responded differently on all growth media but showed general preference to Malt Extract Agar (MEA) with additional of 15% sodium chloride, while 25°C was a preferable growth temperature (p>0.05) by all isolates. All isolates (PR1T4, PP2L4, PR3T13 and PR5T4) cultured in Malt Extract Broth (MEB) displayed significantly (p<0.05) higher antibacterial activity against S. aureus (16.36±0.36mm, 27.57±0.81mm, 22.60±0.62mm and 15.82±0.49mm, respectively) and L. monocytogenes (21.45±0.21mm, 22.34±0.78mm, 21.30±0.50mm and 17.27±0.38mm, respectively) compared to cultures on other media. Ethyl acetate (EA) was the best extraction solvent as crude extracts gave significantly (p<0.05) highest antibacterial activity compared to other solvents. All bacteria shown similar pattern of adhesion on SSD where their log CFU/cm2 readings were increased from 24 to 72 hours. The highest count of adhered cells (log CFU/cm2) on SSD was recorded by E. coli (8.65±0.11) followed by S. aureus (8.14±0.04) and L. monocytogenes (8.01±0.07) while the lowest was displayed by S. typhimurium (7.91±0.08) after 72 hours of incubation. Cell detachment from SSD showed a linear decreased of bacterial counts from 1st to 5th contacts. For example, adhered cell counts (log CFU/cm2) of E. coli reduced from 6.05±0.07 (1st contact) to 0.00 (4th contact) after 24h of incubation. All bacteria except S. typhimurium, showed highest viable counts (log CFU/cm2) (6.80-7.38) on Day 6 and the counts decreased to lowest (3.98-4.25) on the Day 15 while S. typhimurium reached its maximum counts (7.26±0.05) after 9 days of incubation and decreased to 5.10±0.09 on Day 15. In conclusion, all isolates demonstrated promising bioactivities with isolate PR1T4 (P. citrinum) as the most potential candidate to be explored as new antibacterial and biofilm removal agents against food-borne bacteria.